Citizen science shows systematic changes in the temperature difference between air and inland waters with global warming - Weyhenmeyer, Gesa A. (Sci Rep, 2017)
Citizen science projects have a long history in ecological studies. The research usefulness of such projects is dependent on applying simple and standardized methods. Here, we conducted a citizen science project that involved more than 3500 Swedish high school students to examine the temperature difference between surface water and the overlying air (T(w)-T(a)) as a proxy for sensible heat flux (Q(H)). If Q(H) is directed upward, corresponding to positive T(w)-T(a), it can enhance CO(2) and CH(4) emissions from inland waters, thereby contributing to increased greenhouse gas concentrations in the atmosphere. The students found mostly negative T(w)-T(a) across small ponds, lakes, streams/rivers and the sea shore (i.e. downward Q(H)), with T(w)-T(a) becoming increasingly negative with increasing T(a). Further examination of T(w)-T(a) using high-frequency temperature data from inland waters across the globe confirmed that T(w)-T(a) is linearly related to T(a). Using the longest available high-frequency temperature time series from Lake Erken, Sweden, we found a rapid increase in the occasions of negative T(w)-T(a) with increasing annual mean T(a) since 1989. From these results, we can expect that ongoing and projected global warming will result in increasingly negative T(w)-T(a), thereby reducing CO(2) and CH(4) transfer velocities from inland waters into the atmosphere.